Long memory properties and asymmetric effects of emerging equity market: evidence from Malaysia - Abdul Manap, Turkhan Ali; Kassim, Salina (Emerald Group Publishing Limited, 2011)
Purpose – The purpose of this paper is to examine the long memory property of equity returns and volatility of emerging equity market by focusing on the Malaysian equity market, namely the Kuala Lumpur Stock Exchange (KLSE).